“Who Is My Neighbor?” Ethnic Boundaries and the Samaritan Other in Luke 10:25-37 - Keddie, Anthony ca. 20./21. Jh. (Biblical interpretation, 2020)
The story about the “Good Samaritan” in the gospel of Luke appears in the midst of a halakhic discussion between Jesus and a Judaean “lawyer” over who constitutes a “neighbor” (Luke 10:25-37). While scholars have often interpreted this pericope as a call for social inclusivity, the ways that Luke relies on and perpetuates prejudicial Judaean stereotypes about Samaritans have seldom been analyzed. This study draws on social-scientific and critical theory on ethnicity and the plethora of recent scholarship on Samaritan-Judaean interactions in order to explore the ways in which Luke’s text conveys prevalent ethnic stereotypes about Samaritans. It argues that Luke, like earlier and contemporaneous Judaean sources, appropriates an ethnographic representation of Samaritans as “proximate others” as part of a process of identity formation.